GAMBARAN PENGGUNAAN RADIOGRAFI GIGI DI BALAI PENGOBATAN RUMAH SAKIT GIGI DAN MULUT UNIVERSITAS SAM RATULANGI MANADO - Kanter, Mavrits (e-GiGi, 2014)
Abstract: The using of dental radiography had been known as  medium dental science  to helpfully determine diagnose and elected the treatment plan. Dental science education hospital (BP-RSGM Unsrat) is the place where the co-assistant student of dental science continuing their education. All things carry with the standard operating procedure, fill the treatment until the treatment plan done. If we follow the procedure, in particular cases, co-ass student must using radiography to determine the diagnose and treatment plan. The purposes of this research is to describe the using of  dental radiography in BP-RSGM Unsrat. This research tend descriptive method. Data were collected in entire medical records which conduct the patient data radiography who needs the dental radiography in BP-RSGM Unsrat January-December 2012 period, amount of 1710 cases. The results based on the medical records of 63 orthodontic records data, 58 (87.4%) did not use dental radiography. Based on 96 medical records were recorded conservation treatment, 68 (70.8%) did not use dental radiography, which requires a total of only 10% of dental radiographs are using. Medical records were noted abnormalities in the field of oral surgery, oral disease, and none of Periodontology using dental radiographs. Types of intraoral radiographs used 73.7% and entirely using periapical radiographs, and 10 (26.3%) were recorded using medical records and all types of extraoral using panoramic radiographs. Dental radiography is used for enforcement of diagnosis and treatment process and there is no use for the evaluation of treatment. Keyword: Radiography application, intraoral radiography, extraoral radiography     Abstrak: Penggunaan radiografi gigi telah lama dikenal sebagai suatu sarana dalam kedokteran gigi yang sangat membantu dalam penegakan diagnosa dan penentuan rencana perawatan. Balai Pengobatan Rumah Sakit Gigi dan Mulut (BP-RSGM Unsrat) merupakan tempat dimana para mahasiswa profesi melanjutkan studinya. Segala hal diajarkan sesuai dengan prosedur, mulai dari pengisian rekam medik sampai pada perawatan yang dilakukan. Jika mengikuti prosedur, seharusnya pada kasus tertentu, dokter gigi muda harus menggunakan radiografi untuk penegakan diagnose dan rencana perawatan. Tujuan penelitian ini adalah untuk mengetahui gambaran penggunaan radiografi gigi di BP-RSGMP Universitas Sam Ratulangi Manado. Penelitian ini bersifat deskriptif. Pengambilan data dilakukan pada seluruh data rekam medik yang berisi data pasien yang memerlukan radiografi gigi di BP-RSGMP Universitas Sam Ratulangi Januari-Desember 2012,  yang berjumlah 1710. 10% rekam medik menggunakan radiografi gigi. Berdasarkan 63 rekam medik yang mencatat data ortodonti, 58 (87,4%) tidak menggunakan radiografi gigi. 96 rekam medik yang tercatat melakukan perawatan konservasi, 68 (70,8%) tidak menggunakan radiografi gigi, dari keseluruhan yang membutuhkan radiografi gigi hanya 10% yang menggunakan. Rekam medik yang mencatat bidang bedah mulut, penyakit mulut, dan periodonti  tidak satupun yang menggunakan radiografi gigi. Jenis radiografi intraoral yang digunakan 73,7% dan selurunya menggunakan radiografi periapikal, dan 10 (26,3%) rekam medik yang mencatat menggunakan jenis ekstraoral dan semuanya menggunakan radiografi panoramik. Radiografi gigi digunakan untuk penegakan diagnosa dan proses perawatan dan tidak ada yang menggunakan untuk evaluasi perawatan Kata kunci: Penggunaan radiografi, radiografi Intraoral, radiografi Ekstraoral